Beyond the Box : diverging Curatorial Practices - Townsend, Melanie; Bradley, Jessica; Cook, Sarah; Diamond, Sara; Fraser, Andrea; Grenville, Bruce; Katyal, Anjum; Martin, Susan; Medina, Cuauhtémoc; Mesquita, Ivo; Rollig, Stella; Sholette, Gregory; et al. (Banff : Banff Centre Press Banff Walter Phillips Gallery - The Banff Centre for the Arts Banff, 2003)
Beyond the Box : Diverging Curatorial Practices is a collection of essays by leading Canadian and international curators and artists that explores regions of art outside the gallery or museum. Delving into four main topics - Publications, Biennials, Art Museums Today, and New Media - the book documents contemporary curatorial work beyond the boundaries of traditional curatorial practice. The third in a series of books about curatorship, Beyond the Box is sure to be an important touchstone for artists and curators alike. Other books in the series include Naming a Practice : Curatorial Strategies for the Future (edited by Peter White) and The Edge of Everything Reflections on Curatorial Practice (edited by Catherine Thomas)
Man Ray ; Finley, Karen ; Jamie, Cameron ; Tobias, Michael ; Komar & Melamid ; Jaar, Alfredo ; Falk, Gathie ; Tiravanija, Rirkrit ; Green, Renée ; Fraser, Andrea ; Peterman, Dan ; Cutierrez, Marina
Contributors (biog. auteurs) p. 183-187
boek